Penggunaan Media Sosial dalam Pembelajaran Bahasa Arab : Peluang dan Tantangan - Sinta Bella; Mutya Hafidz Raudatun Nisa; Iya Syafiatul Alawiyah (Lembaga Pengembangan Kinerja Dosen, 2025)
The use of social media in Arabic language learning is becoming increasingly significant in today's digital age. Social media has become an integral part of students' and teachers' daily lives, opening up great opportunities to create more interactive, collaborative and engaging learning experiences. WhatsApp, Instagram, Facebook, YouTube and TikTok can increase students' motivation to learn, make materials more accessible, and improve students' Arabic language skills. This study aims to identify the opportunities and challenges of using social media in Arabic language learning using library research method. The results show that social media is often utilized by teachers and students to improve communication, facilitate the distribution of teaching materials, and enrich the Arabic learning experience. The use of social media has also been shown to increase student motivation to learn through active engagement in discussion and collaboration. However, there are some challenges such as unequal access to technology, high potential for distraction, limited internet quota and network problems and digital security risks. The use of social media can be an effective tool in Arabic language learning if integrated with appropriate teaching strategies and accompanied by digital literacy training for teachers and students, as well as the development of creative and safe educational content. This study recommends the development of policies and guidelines for the use of social media in schools and universities, so that the potential of social media in supporting Arabic language learning can be optimally utilized.